Opening Food Distribution hcannel of PT ABC Tbk in Vietnam - Ariesta, Margaretta Septyani; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
Abstract.PT ABC Tbk, founded in 1951, has three main business lines, distribution, manufacturing and support and services, has 5 branches, with head office in Jakarta, and regional offices in Singapore, Thailand, Vietnam and China. Next year, PT ABC Tbk will focus for distribution channel development in Vietnam, cause its contribution is still very small. Euromonitor data highlighted food and beverages market in Vietnam, which is very big with total value around USD 11.7 billion in 2014, and growth rate 14% forecasted, so it is mentioned that Vietnam will be the fastest growing food and beverage ingredients market. PT ABC Tbk, through one of its division, Food Division, will use this opportunity to grow its business by opening new division in Vietnam, Food Distribution Channel, which is selling ingredients to Food Industry. Qualitative research methodology is used in this discussion, by analyzing primary data from internal resources of PT ABC Tbk via management interview, combined with secondary data from Euromonitor International. PT ABC Tbk must define its key success factors and business model for that objective. The key success factors are products chosen for market in Vietnam, experienced local sales force for running daily business, supported with technical expertise to serve customers, and local warehouse, to minimize logistic cost for delivering to customers. Business model that PT ABC Tbk should apply are including customersâ€™ segmentation, value proposition that offered to those customers, which is highlighted product quality and value added ones, beside technical expert service.Keywords: food, ingredients, VietnamÂ Â